Nutritional Status among Children under Five Years in Amman, Jordan - El Azhari, Mohammad; Slaih, Ahmad Abu; S. Khader, Yousef; Al-Musa, Abdulhalim; Iblan, Ibrahim (International Journal of Child Health and Nutrition, 2017)
Objectives: There is scarcity of data on malnutrition among children in Jordan. Therefore, this study was conducted to assess the nutritional status and estimate the prevalence rates of stunting, underweight, and wasting and their associated factors among children under five. Subjects and Methods: A cross-sectional study was conducted between January and April 2017 among children under five years in Amman, Jordan. All Jordanian children under five years who visited the selected health centers for vaccination or accompanied their mothers during the study period were included in this study. Mothers or caregivers of children were interviewed face-to face using the study questionnaire. Weight in kilograms and height in centimeters were measured for all children. Anthropometric indices were calculated using reference medians recommended by the World Health Organization. Results: This study included a total of 923 (463 boys and 460 girls) children. The prevalence rates of stunting, underweight, and wasting were 6.2%, 3.8%, and 2.8%, respectively. Multivariate analysis showed that low birth weight was significantly associated with stunting (OR = 2.9, 95% CI: 1.4,6.0; p-value=0.003) and underweight (OR =5.6, 95% CI: 2.5,12.3, p-value <0.001). Compared to exclusive breastfeeding, mixed feeding was associated with increased odds of stunting (OR =2, 95% CI: 1.1-3.9, p-value =0.029) and underweight (OR = 2.2, 95% CI: 1.002, 5.0; p = 0.049). None of the variables were significantly associated with wasting. Conclusions: The prevalence rates of stunting, wasting and undernutrition among children under five years in Jordan are low. Low birth weight and mixed feeding were associated with higher rates of malnutrition.